Renal Safety of Tenofovir Alafenamide versus Tenofovir Disoproxil Fumarate for the Treatment of Chronic Hepatitis B Patients: An Evidence-based Case Report - Dewi, Putu Itta Sandi Lesmana; Pamungkas, Kadek Mercu Narapati; Mariadi, I Ketut (The Indonesian Society for Digestive Endoscopy, 2024)
ABSTRACTBackground: Treatment modalities for chronic hepatitis B infection (CHB) are interferon and antiviral. The most commonly used antiviral is tenofovir disoproxil fumarate (TDF), however it is known to have nephrotoxicity. Recently, a new antiviral tenofovir alafenamide (TAF) has been developed, which also inhibits hepatitis B virus (HBV). This study aimed to compare the renal safety of TAF and TDF.Method: Literature searching was conducted in PubMed/Medline and Cochrane databases, with modified keywords as “chronic hepatitis B”, “tenofovir alafenamide”, “tenofovir disoproxil fumarate”, “renal” with BOOLEAN logic. The articles obtained will be selected and will be carried out for critical appraisal about validity, importance, and applicability.Results: Four studies of double-blind randomized-clinical trials (RCT) were obtained for analysis. The antiviral effects of TAF and TDF groups were not significantly different. The increase in serum creatinine of TAF group was significantly smaller than TDF group in three studies (p 0.05). While one study showed no significant difference (p = 0.32). The decrease in eGFR (estimated-Glomerular Filtration Rate) in the TAF group was smaller than TDF in three studies (p 0.001), whereas one study found an increase in eGFR in the TAF group (p = 0.00034). There were no severe side effects found in both study groups.Conclusion: Based on the scientific evidence obtained, TAF has more renal safety than TDF. Although the antiviral effect is not significantly different. Keywords: chronic hepatitis B, tenofovir alafenamide, tenofovir disoproxil fumarate, renal function